The Normative Nature of Aggressive Intrusive Thinking Among an Underserved Incarcerated Population Compared With a Student Sample - DeLapp, Ryan C. T. (International journal of offender therapy and comparative criminology, 2018)
Aggressive intrusive thoughts (AITs) are unwanted and repetitive thoughts, impulses, or desires that enter into consciousness involuntarily. The current study compared the frequency of and distress from AITs in a sample of inmates jailed for violent crimes (n = 78) versus college students (n = 103; that is, participant status). The relationship between psychopathic traits and AITs was also explored. Results indicated that, although there were no differences between students and inmates, AIT frequency was positively associated with Primary Psychopathy. However, there was no significant interaction between participant status (i.e., inmate vs. student) and psychopathy. Finally, there were no significant main or interactions effects in the model predicting AIT distress. These findings demonstrate that AIT frequency is a normative cognitive experience that occurs in both nonviolent and violent individuals, and provides further evidence for an association between psychopathic traits and unwanted aggressive cognition.